Profesionalisme Amil Zakat Dalam Mewujudkan Kesuksesan Zakat - Sirait, Frida Yanti; Nasution, Yenni Samri Juliati (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
Currently, zakat management has become a necessity for the entire community, especially Muslims. Professional zakat management will increase the community's capacity to achieve prosperity when noble social entrepreneurship is known to the public. The aim of the research is to determine the professionalism of zakat amil in realizing zakat success. The research method is literature study (Library Research). The results of the research are Amil zakat. Development of amil zakat is carried out in various ways such as providing knowledge of zakat fiqig, providing knowledge of calculating zakat as well as public speaking training to increase stakeholder trust in the accountability and compliance of zakat management organizations through zakat amil institution. The professionalism of amil zakat is not only sharia knowledge about ZIS (Zakat, Infaq and Alms) but also in relation to management. An amil must have work professionalism, including: Amil zakat must understand the struggle for zakat (Fikih Zakat) completely and in depth, Amil zakat must understand the concepts and practices of zakat management, Amil Zakat must understand the basic and practical concepts of accounting and accountability, and be involved in the Association Amil Zakat.